2012
DOI: 10.4315/0362-028x.jfp-12-148
|View full text |Cite
|
Sign up to set email alerts
|

Health Department Inspection Criteria More Likely To Be Associated with Outbreak Restaurants in Minnesota

Abstract: Millions of routine restaurant inspections are performed each year in the United States, and the Centers for Disease Control and Prevention has reported that a majority of foodborne illness outbreaks occur in restaurant settings. In an attempt to relate the data collected during inspections in Minnesota to illness likelihood, data from routine inspections conducted at outbreak restaurants were compared with data from routine inspections conducted at nonoutbreak restaurants. The goal was to identify difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The number of correct responses was very low (88.6% scored less than four out of nine), and respondents responded as follows: differentiating between FBD and FBD outbreak (13.1%), importance of conducting outbreak investigation (14.8%), activities at the outbreak site (16.4%), maintaining the cold chain (18.0%), chain of custody (31.1%) and time frame to finalise and provide feedback (29.5%). This could impair on the urgency of conducting an outbreak investigation, as these differ from routine inspections (Petran, White & Hedberg 2012 ). Such conduct might lead to failure in determining the environmental factors that contributed to the occurrence of an outbreak, and may have detrimental consequences such as failure to prevent further outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…The number of correct responses was very low (88.6% scored less than four out of nine), and respondents responded as follows: differentiating between FBD and FBD outbreak (13.1%), importance of conducting outbreak investigation (14.8%), activities at the outbreak site (16.4%), maintaining the cold chain (18.0%), chain of custody (31.1%) and time frame to finalise and provide feedback (29.5%). This could impair on the urgency of conducting an outbreak investigation, as these differ from routine inspections (Petran, White & Hedberg 2012 ). Such conduct might lead to failure in determining the environmental factors that contributed to the occurrence of an outbreak, and may have detrimental consequences such as failure to prevent further outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that it is especially challenging to use short duration visual inspection to monitor faults in staff personal hygiene (Leisner et al 2014 ). Petran and colleagues (Petran et al 2012 ) could find correlations between hygienic level and outbreaks in restaurants when outbreaks caused by NoV, Clostridium or Salmonella were investigated based on as many as 54 criteria. According to them, 50% of the relevant criteria were related to food handling, 37% to facilities and 15% to personal hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate control measures and guidance on hygienic practices were implemented to prevent further cases. Hygienic inspections among food operators efficiently corrected actions as in [34,35]. The withdrawal of two days from work since the clearance of gastrointestinal symptoms is a commonly used measure [36,37], and there are presumably constraints to lengthen this.…”
Section: Discussionmentioning
confidence: 99%